2007
DOI: 10.1002/mrc.2058
|View full text |Cite
|
Sign up to set email alerts
|

NMR and IR characterization of the aluminium complexes of norfloxacin and ciprofloxacin fluoroquinolones

Abstract: A set of new aluminium complexes of norfloxacin (NOR) and ciprofloxacin (CIP) that show an improvement in their pharmaceutical properties were studied using solution and solid-state nuclear magnetic resonance (NMR) and infrared (IR) spectroscopy. The complexes synthesized with two different methods were compared. One of these methods will allow formulation of the compounds at production scale. High-resolution (13)C spectra were obtained with the cross-polarization and magic angle spinning (CP-MAS) experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
5
23
0
2
Order By: Relevance
“…This hypothesis agrees with the 13 C CP-MAS spectrum of complex 3, which is very similar to the spectrum of 1 and 2 in the 160-180 ppm region, showing two signals that are assigned to the carbon atoms directly bonded to the oxygen atoms linked to rhenium. 22 The IR spectra also agrees with the proposed coordination for ciprofloxacin, showing two intense signals at 1614 and 1480 cm -1 , in concordance with the observed values for complexes 1-2, and with reported data for other complexes with this coordination. 19,29,54 No signal was observed at 1730 cm -1 , showing that this complex is free of contamination with ciprofloxacin and two intense peaks, assigned to the characteristic υ(CO) absorptions of the fac-{Re(CO) 3 } fragment,…”
Section: Rhenium (I) Complexsupporting
confidence: 90%
See 1 more Smart Citation
“…This hypothesis agrees with the 13 C CP-MAS spectrum of complex 3, which is very similar to the spectrum of 1 and 2 in the 160-180 ppm region, showing two signals that are assigned to the carbon atoms directly bonded to the oxygen atoms linked to rhenium. 22 The IR spectra also agrees with the proposed coordination for ciprofloxacin, showing two intense signals at 1614 and 1480 cm -1 , in concordance with the observed values for complexes 1-2, and with reported data for other complexes with this coordination. 19,29,54 No signal was observed at 1730 cm -1 , showing that this complex is free of contamination with ciprofloxacin and two intense peaks, assigned to the characteristic υ(CO) absorptions of the fac-{Re(CO) 3 } fragment,…”
Section: Rhenium (I) Complexsupporting
confidence: 90%
“…Thus, in free ciprofloxacin a sole signal is observed that has been assigned to the carboxylate and C4 carbon atoms. 22 The coordination of the metal through the oxygen atoms of carbonyl and carboxylate groups exerts a strong influence on these carbon atoms directly bonded to these oxygen and these resonances are observed in the complex 1 as two different peaks. This assignment is consistent with the reported study with complex [Al(CpfH) 3 ]Cl 3 (CpfH = ciprofloxacin).…”
Section: Dna Gyrase Cleavage Assaymentioning
confidence: 99%
“…In some case, NFX can also act as bridging ligands and to form polynuclear complexes with metal ion. Combining with FTIR spectra and reported literatures, the complexation of NFX and Fe-MCM-41 was believed to through the 3-carboxylic group [27,28]. The peak observed at 1476 cm À1 (attributed to aromatic ring) and the strength of peak at 1636 cm À1 might suggest the existence of other adsorption affinity such as electrostatic interaction, p-p interaction, and hydrophobic effect (discussed later).…”
Section: Effect Of Silicon-iron Ratiomentioning
confidence: 85%
“…The CIP-SAC (I and II) spectra were assigned comparing with the previously reported 13 C CP/MAS spectra of CIP and SAC, and taking into account the NQS data of each compound (see Fig. 8) Chattah et al, 2007).…”
Section: Ir Spectroscopymentioning
confidence: 99%